IRONI DALAM NOVEL THE PEARL OLEH JOHN STEINBECK - ALLO, MELIWATI RINDA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT This research is entitled â€œ Ironi dalam Novel The Pearl karya John Steinbeck.â€ In this research, the writer focuses on irony in plot and characters in the novel. This novel is one of John Steinbeckâ€™s works and it is famous in Amerika, 1947. In this research, the writer uses instrinsic approach to understand about plot and characters in the novel. Parts of research explained the types of irony, which are Verbal Irony, Dramatic Irony, and Situational Irony. The purpose of this research is to identify, analyze, and describe the types of irony in the novel. This research is also done because there are elements of real life that also occur in this novel. The results of this study contain three types of irony, which are Verbal Irony, Dramatic Irony, and Situational Irony. Verbal Irony is a conversation between Kino and the pearl buyer, Dramatic Irony describes the events that made Coyotito die, and Situasional Irony illustrates a Kino delusion that wants a better life than ever before. Â Keywords : Irony, The Pearl, John Steinbeck, Characters, Plot, Intrinsic approach